Chemical composition, actividad larvicide, insecticide and repellent of essential oil Aedes aegypti (Research, Society and Development, 2022)
Dengue is transmitted by the mosquito Aedes aegypti, which is controlled by insecticides and repellents. The plant-based essential oils are used as excellent repellents. Therefore, the present review is essential for understanding the efficacy of essential oils against mosquitoes. The articles related to essential oils were searched from 2014 to 2022 in Pubmed, Science Direct, LILACS, Scielo, and Google Scholar using the following keywords-essential oil, Aedes aegypti, and repellents. A total of 280 plants were extracted for EOs from 33 families. The most plants belong to Lamiaceae (45.4%), followed by Myrtaceae (38.3%) and Rutaceae (28.4%). The metabolites in EOs with the maximum repellent/larvicidal activity include β - caryophyllene, α - pinene, 1,8 - cineol, linalool, and eugenol, the lethal concentrations ranged from 40 to 120 ppm. These results support the view that essential oils are promising in the formulation of repellents, larvicides, insecticides, and pesticides.